A recent jet impingement PVT collector technique developed (reversed circular flow jet impingement): energy and exergy analysis - Muhammad Amir Aziat Ishak,; Adnan Ibrahim,; Lim, Yun Seng; Djebara Amel,; Noui Zouheyr, (Penerbit Universiti Kebangsaan Malaysia, 2024)
When subjected to solar irradiance, the upsurge in photovoltaic (PV) module temperature has constrained the photovoltaic thermal (PVT) technology’s ability to generate electrical power, thereby affecting its overall PVT efficiency. Jet impingement has proven to be a viable method in improving a PVT collector’s efficiency. This research functions as an extension to the existing established reversed circular flow jet impingement (RCFJI) PVT collector. The present study performed an in-house study to investigate the energy and exergy characteristics of the RCFJI PVT collector outlet configuration. The RCFJI outlet hole was configured into five distinct design settings: one hole (1h), two holes (2h), three holes (3h), four holes (4h), and five holes (5h). The experiment was executed with a uniform irradiance level of 900 W/m2 and flow rate varying from 0.01-0.14 kg/s. As a result, the peak photovoltaic and thermal efficiency achieved using the 1h configuration was 11.09% and 63.2% at 0.14 kg/s. Particularly, the 1h configuration yielded an overall PVT efficiency of 72.35%. The study noted that the optimal flow rate was 0.06 kg/s, leading to the highest exergy of 12.32%. In a nutshell, increasing the RCFJI outlet numbers does not favourably impact the energy efficiency of the RCFJI PVT collector. The significance of this study contributes to the understanding of outlet configuration effects on the RCFJI performance.